ECONOMIC INSTRUMENTS IN WASTE MANAGEMENT IN THE RURAL REGIONS IN SOUTH EEAST EUROPE - Grbić, Vladimir; Todić, Dragoljub (Economics of Agriculture, 2011)
The main aim of this paper is to analyze the problems of waste management in the rural regions in the Southeast Europe and to identify the economic instruments for their solving. It is concluded that waste production in those countires have been increased approching to average level realised in the EU, as well there are no collection and waste treatmant in the rural regions. A set of the economic instruments for the solving those problems are sugested. In their base is the polluted pays principle. It supposes the cost recovering principle,that is , above all, to set up the public utility services and the cost recovery in the rural regions by themselfs. In this paper are also indetifed the sources for the fnancing investments in those activitis and confrm necesity for completing environmental law regulations.